Studi Pengaruh Geometri Peledakan terhadap Biaya Pemboran dan Biaya Peledakan pada PT Unggul Dinamika Utama Kabupaten Kutai Timur Provinsi Kalimantan Timur - Berliani Wahyu Ningrum; Tommy Trides; Rety Winonazada; Revia Oktaviani; Lucia Litha Respati (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the effect of blasting geometry on drilling and blasting costs in mining operations at PT Unggul Dinamika Utama, Kutai Timur Regency, East Kalimantan Province. The research focuses on comparing two operational areas, namely PIT Tempudo 6 and PIT East, which apply different blasting geometries: a burden of 7 m and spacing of 8 m at PIT Tempudo 6, and a burden of 8 m and spacing of 9 m at PIT East. The research method involved collecting primary data from actual field drilling and blasting activities, as well as secondary data from the company. The parameters analyzed included blasting geometry, explosive consumption, and operational costs of drilling and blasting. The results show that the total drilling cost at PIT Tempudo 6 was Rp. 215,689,696, while at PIT East it was Rp. 162,177,899. The total blasting cost at PIT Tempudo 6 reached Rp. 3,023,066,977.60, while at PIT East it was Rp. 1,780,839,602.80. Thus, the total operational cost of blasting activities at PIT Tempudo 6 amounted to Rp. 3,238,756,673.60, and at PIT East amounted to Rp. 1,943,017,501.80. It can be concluded that differences in blasting geometry significantly affect operational cost efficiency. Larger burden and spacing values lead to more efficient costs by reducing the number of drill holes and explosive consumption per blasted rock volume.